Young child with painful edema and purpura: a case report - Sarah Contorno; Giorgio Cozzi; Irene Berti; Egidio Barbi; Andrea Taddio (BMC, 2021)
Abstract Background We reported the case of a two-old-year boy with a painful acute hemorrhagic edema. This is a self-limited benign condition: usually, affected children are well appearing and this strongly support the diagnosis. In the opposite, in our case, we observed a painful presentation of the edema. Therefore, we demonstrated that rarely, this condition could have also a painful presentation. Conclusions This case report helps clinician to know that also acute hemorrhagic edema could have a painful presentation, so we must considered it in the differential diagnosis with sepsis, sickle cell crisis and child abuse. We believe that these findings will be of interest to pediatricians.